Underrepresentation, Quotas and Quality: A Dynamic Argument for Reform - Malin Arve; Justin Valasek (Center for Economic Studies and ifo Institute (CESifo), 2023)
The trade-off between increased representation and perceived quality is central to the debate on how to address underrepresentation in high-profile professions. We address this trade-off using a dynamic model of career selection where juniors value both the identity and perceived quality of their mentors (seniors). A preference for homophily results in the persistence of underrepresentation, suggesting intervention is needed. However, if an abrupt quota causes a large decrease in the perceived quality of underrepresented seniors, then underrepresented juniors of high talent will select out of the profession, causing a permanent (real) quality difference. Encouragingly, we show that gradual reform—while decreasing perceived quality in the short term—enables a transition to equal representation and equal quality in the long term. We discuss the implications of our analysis for commonly-used measures to increase representation.
Keywords: D62; E24; I20; J15; J16; J24; 330; affirmative action; quotas; mentorship; identity; gender; adverse selection